IQTIBAS : Mendeteksi Prosa dan Syair dalam Al-Qur’an dan Hadis - Abdurrahman Abdurrahman; Mirsa Triandani; Harun Al Rasyid (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
A few centuries after the demise of the Qur'an, the scholars formulated language, usub and literature in order to study and deepen the content of the Qur'an, which gave rise to many scientific disciplines, among others in the field of language studies, nahwu and sorof , related to the style of language and literature was born balaghoh discipline with branches of study, ma'ani, bayan and badi '. In Badi Science, iqtibas is defined as follows "The speaker saves his prose or poem with something from the Qur'an or Hadith in a way that does not signal that something comes from both." Qaidah The science of Badi allows mutakallim (speaker) to change a little on the word taken from the Qur'an or Hadith, that is due to the adjustment of wazan or other causes. Iqtibas with the text of the Qur'an and sunna is not prohibited and forbidden in absolute terms, it is permissible but must be with caution.